Comprehensive In Silico Analysis Of Bioactive Compounds From Pyrrosia piloselloides Leaves As Xanthine Oxidase Inhibitors - Sinuhaji, Masira Sony Crespo; Havid, Husnul; Ysrafil, Ysrafil; Alexandra, Francisca Diana (Universitas Padjadjaran, Indonesia, 2025)
This study aimed to evaluate the potential of bioactive compounds from Pyrrosia piloselloides leaves as xanthine oxidase (XO) inhibitors through an in silico approach. Methods included molecular docking and molecular dynamics simulations to identify the binding affinity of test compounds to XO. Among 59 screened compounds, 3 compounds (2,6,10,14,18,22-Tetracosahexaene, 6-Hydroxymethaqualone, and β-Sitosterol acetate) exhibited the lowest binding energy in comparison to the control, Allopurinol, with key residue contributions from GLU 802, ARG 880, and THR 1010. Molecular dynamics simulations confirmed the interaction stability, with β-Sitosterol acetate showing the lowest total binding free energy (-46.23 ± 0.66 kcal/mol). ADMET predictions revealed promising pharmacokinetic profiles for these compounds. This study highlights Pyrrosia piloselloides as a promising source of novel XO inhibitors, with further validation required through in vitro and in vivo experiments.